Genetic Algorithm-Optimized Adaptive Network Fuzzy Inference System-Based VSG Controller for Sustainable Operation of Distribution System - Othman M.H.; Mokhlis H.; Mubin M.; Ab Aziz N.F.; Mohamad H.; Ahmad S.; Mansor N.N. (MDPI, 2023)
alternative energy; electricity supply